The Relationship Between the Frequency of Infant Massage and the Increase in Body Weight of Infants Aged 6–18 Months at Ralla Community Health Center, Barru Regency - Rizky Auliah Juniarti; Fitratunnisah Fitratunnisah; Aminah Ali (Lembaga Pengembangan Kinerja Dosen, 2025)
Infant growth and development can be monitored through anthropometric measurements, particularly body weight. Infants with low birth weight (LBW) (< 2500 grams) are at risk of growth disorders. One form of stimulation that can promote infant weight gain is infant massage. This study aimed to determine the relationship between the frequency of infant massage and the increase in body weight of infants aged 6–18 months at Ralla Community Health Center, Barru Regency. This was a quantitative study with a retrospective design. Resulting in 27 infant respondents. The results showed that most respondents received infant massage frequently (88.9%), and 24 infants experienced weight gain (88.9%). Fisher’s Exact test yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between the frequency of infant massage and the increase in body weight of infants aged 6–18 months at Ralla Community Health Center. This study recommends that parents routinely practice infant massage to optimize infant growth and development, and encourages further research on other factors influencing infant body weight.